Long range chromatin organization: a new layer in splicing regulation? - Gómez Acuña, Luciana Inés (2014)
Splicing is a predominantly co-transcriptional process that has been shown to be tightly coupled to transcription. Chromatin structure is a key factor that mediates this functional coupling. In light of recent evidence that shows the importance of higher order chromatin organization in the coordination and regulation of gene expression, we discuss here the possible roles of long-range chromatin organization in splicing and alternative splicing regulation.